A coating of chitosan and propolis extract for the postharvest treatment of papaya (Carica papaya L. cv. Hawaiiana) (2015)
Propolis is a natural antimicrobial that can be used asa bioadditive in coatings to control fruit quality losses. The effectof two coatings was evaluated, a control (chitosan, 1%) and atreatment (chitosan, 1%; containing propolisethanolic extract, 5%),on the microbiological and physicochemical properties of papayafruits. The chemical profile of the propolis revealed the presenceof fatty acids and their esters, carbohydrates, diterpenic acids,and pentacyclic triterpenes. The fruits covered with the treatmentdemonstrated a reduced deterioration index and infection diameterof the fungus Colletotrichum gloeosporioides, as compared tothe control papayas, postponing the appearance of damage bytwo days. Additionally, the treatment did not significantly affectthe physicochemical properties of the papaya, as compared tothe control. In conclusion, the coating formulated with propolisexhibited an in situ fungicidal and bactericidal effect withoutaltering the physiological changes of the papaya fruit duringstorage.